PERKEMBANGAN DEMOKRASI DI INDONESIA:ANALISIS HUBUNGAN LEGISLATIF DAN EKSEKUTIF 1950 - 1992The Development of Indonesia's Democracy: An Analisys onthe Relationship of Legislative and Executive (1950 - 1992 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
The purpose of this research is to describe the development of Indonesia's democracy, particularly the role of its legislative when it was faced with its executive during the period of 1950 -1992.The result of this research shows that during 1950 - 1957 period, Indonesia's legislative had playing its role optimally and had strong bargaining power, particularly when it was faced with executive power. This fact can be proved by its intensity to perform its rights of both constitutional and control function. Therefore, it can be concluded that the performance of Indonesia's democracy during this period was quite well.Yet during the period of 1957 -1992, particularly beginning the declaration of martial law, in March 1957, the role of legislative was declining. It can be proved by the declining of its rights in performing both constitutional and control function. It did not have a strong bargaining power. This condition implies that the performance of Indonesia's democracy was declining.The declining role of Indonesia's legislative was caused by the political policy which was made by Indonesian elite. Elite had made the legislative was in inferior position vis-a-vis the executive in deciding political policies. The dominant position of Indonesia's executive was supported by the model of Bureaucratic Polity - that is, a political system in which power and participation in national decisions are limited almost entirely to the employees of the state, particularly the officer corps and the highest levels of the bureaucracy.